Analisis Dampak Game Online Terhadap Kehidupan Sosial Anak: Penelitian - Muhammad Rizal Fahmi; Fidiatul Adiyan; Ina; Andrian (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this study is to analyze the impact of online games on children's social lives. The research method is qualitative. Data collection techniques include observation, documentation, and interviews. The data collection technique for research subjects uses purposive sampling. The results of the study are: (1) children prefer to be alone so as not to be disturbed while playing games; (2) it is difficult to communicate well. This is because children rarely communicate with people directly; (3) children try to show their abilities and superiority in social interactions through online games; (4) children often use foul language when playing online games.